Analisis Kinerja PLTS 200WP Secara Realtime Menggunakan IoT - Yosi Apriani; Muhammad Alfarizi; Zulkifli Saleh; Wiwin A Oktaviani; Krisna Nata Wijaya (Jurnal Ampere, 2023)
Technological developments occur in various ways, for example wireless communication technology, computer networks and the internet, designing monitoring and control systems based on the Internet of Things (IoT). The application of the IoT concept has been widely carried out with various studies in various fields of life including analyzing solar panels in real time which can be done by utilizing the development of micro and wireless and internet-based control technology called IoT. The performance of a PLTS can be assessed by calculating the efficiency of the PLTS components themselves. The purpose of this study is to analyze the performance of a 200Wp PLTS from IoT-based Blynk application data. The methodology used in this study starts from 1) tool design; 2) tool making; 3) tool testing; 4) evaluation. From the results of the study it was found that the efficiency of solar panels was 11.35% The efficiency of SCC was 93%, the efficiency of Baerai was 94.8%, the efficiency of inverters was 92.6%, and the total efficiency of PLTS was 9.29% . The efficiency of this PLTS is considered low for a 200Wp PLTS